2021
DOI: 10.3389/fcell.2021.768943
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Drug-Eluting Bead Bronchial Arterial Chemoembolization Plus Anlotinib in Patients With Advanced Non-small-Cell Lung Cancer

Abstract: Aim: The aim of this study is to determine the efficacy and safety of the combination therapy of drug-eluting bead bronchial arterial chemoembolization plus anlotinib oral administration in the treatment of non-small-cell lung cancer (NSCLC).Methods: Consecutive data from 51 patients with advanced NSCLC were retrospectively collected from February 2018 to August 2019. All patients underwent drug-eluting bead bronchial arterial chemoembolization (DEB-BACE) followed by anlotinib treatment. Overall survival (OS) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…Liu et al reviewed 51 patients with advanced (III-IV) NSCLC who underwent DEB-TACE plus BAI followed by treatment with anlotinib, an oral tyrosine kinase inhibitor that inhibits vascular endothelial growth factor receptor, platelet-derived growth factor receptor, fibroblast growth factor receptor, and tyrosine kinase. 34 Chemotherapy regimen was selective arterial injection of pemetrexed/cisplatin for adenocarcinoma and gemcitabine/ cisplatin for squamous cell carcinoma followed by pirarubicin-loaded beads followed by Gelfoam particles. Three to six cycles of the procedure were performed for all patients as indicated by contrast-enhanced CT every 6 to 8 weeks.…”
Section: Results Of Tace Combined With Bai and Systemic Therapiesmentioning
confidence: 99%
“…Liu et al reviewed 51 patients with advanced (III-IV) NSCLC who underwent DEB-TACE plus BAI followed by treatment with anlotinib, an oral tyrosine kinase inhibitor that inhibits vascular endothelial growth factor receptor, platelet-derived growth factor receptor, fibroblast growth factor receptor, and tyrosine kinase. 34 Chemotherapy regimen was selective arterial injection of pemetrexed/cisplatin for adenocarcinoma and gemcitabine/ cisplatin for squamous cell carcinoma followed by pirarubicin-loaded beads followed by Gelfoam particles. Three to six cycles of the procedure were performed for all patients as indicated by contrast-enhanced CT every 6 to 8 weeks.…”
Section: Results Of Tace Combined With Bai and Systemic Therapiesmentioning
confidence: 99%
“…This indicates that these regimens are promising approaches and can be tolerated by patients with STRI-SCLC. For patients with advanced NSCLC, Liu et al (18) reported a median PFS of 8.4 months and a median OS of 18.4 months for those treated with DEB-BACE plus anlotinib and indicated that DEB-BACE concomitant with anlotinib is effective and well-tolerated by these patients. An identical result was also observed in the present study, in which postoperative anlotinib was analyzed as the predictor of OS in patients with STRI-SCLC treated with DEB-BACE.…”
Section: Discussionmentioning
confidence: 99%
“…An identical result was also observed in the present study, in which postoperative anlotinib was analyzed as the predictor of OS in patients with STRI-SCLC treated with DEB-BACE. The potential mechanisms of the longer OS resulted from postoperative anlotinib were the following: (I) an embolization-induced hypoxic environment may increase the risk of recurrence and stimulate neovascularization of peritumoral tissue (18); and (II) anlotinib could inhibit the tumor angiogenesis and enhance the synergistic anticancer effects of DEB-BACE. This study has several limitations that should be noted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first-line treatment for NSCLC is chemotherapy [ 6 ]. Arterial chemoembolization has been widely used in clinical practice because of its good efficacy in treating NSCLC and advantages of less trauma and less toxic side effects compared with intravenous systemic chemotherapy [ 7 ]. In recent years, minimally invasive interventional therapy for solid tumors is developing rapidly.…”
Section: Introductionmentioning
confidence: 99%